Importancia de la implementación de protocolos institucionales para el uso de albúmina - Pineda L., Rafael; Jirón A., Marcela; Sánchez I., Paz (Revista Hospital Clínico Universidad de Chile, 2012)
Intravenous fluid administration to maintain or restore fluid balance is a common intervention whithin a hospital. The choice between cristaloids or colloids affects patient outcome. Albumin is an important and expensive therapeutic tool, with as many clinical advantages as controversial costs associated. Evidence indicates that only in certain indications, albumin is cost-effective and its effects in many treatments are equally effective than cristaloids, an alternative much less expensive. The SAFE study, a large, multi-centre, randomized blind trial, in intensive care units (ICU) units, suggests that use of albumin or saline solution gives similar outcomes, regardless patient’s baseline serum albumin concentration. Since firsts attempts to implement protocols in albumin use, hospitals have seen many cases of unproper albumin utilization, decrease in albumin utilization, and savings in medication costs, with no effects on mortality in ICU patients. At Clinical Hospital of Universidad de Chile, an albumin protocol has been developed and has been developed an implemented since 2008. Its effects in level and use tendencies before and after protocol, costs shifts, and albumin utilization, are subjects of research.